KRITIK SOSIAL TERHADAP SISTEM HUKUM DALAM NOVEL BUKAN KARENA KAU KARYA TOHA MOHTAR (Sebuah Tinjauan Sosiologis) - Waluyo, Sukarjo (Faculty of Humanities, Diponegoro University, 2014)
The research entitled â€œ Critical Social of Law System in The Novel Bukan Kerena Kau, by Toha Mohtar (A Sociological Analysis)â€ intends to tell the critical social in law system which has been occurredÂ at that time as the novel written. Critical social is one of literature critics which specially studies literature using social aspects in its consideration. Sociologically, BKK novelÂ is a very interesting novel because it is able to tell the critical social in its story. In the novel, we can see the poor of social livingÂ situation and condition . It is in line with Indonesia history which the people have just been independent. The critical social ofÂ law systemÂ has not revealed the involvement of law as a social control device and a means to expedite the process of social interaction.